Green On-Site Diclofenac Extraction from Wastewater Matrices Using a 3D-Printed Device Followed by PTV-GC-MS Determination - César Castro-García; Edwin Palacio; Rogelio Rodríguez-Maese; Luz O. Leal; Laura Ferrer (Chemosensors)
A 3D-printed device was designed and printed by a stereolithographic technique (SLA) and coated with a highly selective solid phase extraction resin for on-site diclofenac extraction from wastewater, avoiding the transport and treatment of large volumes of samples in the laboratory. The best results in terms of chemical and mechanical resistance were obtained with Rigid 10K resin. The “stick-and-cure” impregnation technique was used to coat the 3D-printed device with Oasis® HLB resin. The coated 3D-printed device can be reused up to eight times without losing extraction efficiency. The eluent and derivatization reagent volumes were optimized by a multivariate design. The proposed method allowed for the extraction and determination of diclofenac by PTV-GC-MS, achieving methodological detection and quantification limits of 0.019 and 0.055 μg L−1, respectively, with a preconcentration factor of 46. The analysis time was 23 min per sample. To validate the proposed methodology, addition/recovery tests were carried out in different wastewater samples, obtaining recoveries above 90%. The methodology was applied at the wastewater treatment plant (WWTP) of Calvià (Mallorca, Spain), finding diclofenac in concentrations of 15.39 ± 0.07 μg L−1 at the input of the primary decantation process, 4.48 ± 0.03 μg L−1 at the output of the secondary decantation, and 0.099 ± 0.001 μg L−1 at the output of the tertiary treatment, demonstrating the feasibility of the on-site extraction method in monitoring diclofenac over a wide concentration range. Finally, a greenness index of 0.58 for the proposed on-site sample preparation was achieved according to the AGREEprep metrics, making it an eco-friendly alternative for diclofenac monitoring.